On Producer Taxation - Mirrlees, J. A. (Review of Economic Studies, 1972)
Journal Article On Producer Taxation Get access J. A. Mirrlees J. A. Mirrlees Nuffield College, Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 39, Issue 1, January 1972, Pages 105–111, https://doi.org/10.2307/2296447 Published: 01 January 1972